2020
DOI: 10.24313/jpbl.2020.00255
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Practical Application of Problem-Based Learning to a Major Class of Dental Hygienics: Focused on the Clinical Dental Hygienics Subject

Abstract: Recently, demands for a new image of man within society also led to calls for change in approaches to education (Hangyo, 2006). Increases in available information and access to knowledge are evident in our society. While schools are often the primary sources of information, it has become more and more impossible to apply and utilize that information in actual life (Hwang, 2002). In modern times, it is meaningless to make knowledge acquisition and simple memorization of details as the main objectives of educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Articles submitted to this journal report that policy developers across the world have set directions for educational change in pursuit of graduate outcomes that better prepare professionals for the future (Park et al, 2020;Zumbach et al, 2020;Byun, 2020;. Byun (2020) cited the World Economic Forum (WEF) proceedings where in 2017 it was suggested that ten skills were required to thrive in the Fourth Industrial Revolution: Complex Problem Solving, Critical Thinking, Creativity, People Management, Coordinating with Others, Emotional Intelligence, Judgment and Decision Making, Service Orientation, Negotiation, and Cognitive Flexibility.…”
Section: The Demand For Educational Changementioning
confidence: 99%
“…Articles submitted to this journal report that policy developers across the world have set directions for educational change in pursuit of graduate outcomes that better prepare professionals for the future (Park et al, 2020;Zumbach et al, 2020;Byun, 2020;. Byun (2020) cited the World Economic Forum (WEF) proceedings where in 2017 it was suggested that ten skills were required to thrive in the Fourth Industrial Revolution: Complex Problem Solving, Critical Thinking, Creativity, People Management, Coordinating with Others, Emotional Intelligence, Judgment and Decision Making, Service Orientation, Negotiation, and Cognitive Flexibility.…”
Section: The Demand For Educational Changementioning
confidence: 99%